COMPARISON OF THE EFFECTS OF ANTIDEPRESSANTS ON COGNITION FUNCTIONS IN PATIENTS OF MAJOR DEPRESSIVE DISORDERS IN TERTIARY CARE HOSPITAL IN HARYANA - RANI, SEEMA; SINDHU, NITIKA; SAINI, RAHUL; PANDEY, A.K; NARWAT, ARVIND; GARG, SUNNY (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Depression is one of the most common mood disorders. Patients with major depressive disorder (MDD) usually present alterations in various cognitive functions. Several cost-effective interventions have shown favorable recovery and positive outcomes in the care and management of depression. The objective of the study was to compare the effect of fluoxetine (selective serotonin reuptake inhibitors), and venlafaxine (serotonin-norepinephrine reuptake inhibitors) on cognitive functioning in patients with MDD. Methods: This prospective, single-blinded, randomized, and comparative interventional clinical study was conducted in a tertiary care hospital in Haryana. Fifty-two patients of MDD (ICD-10) were randomly divided into two groups: Group F and Group V, allocated to receive fluoxetine and venlafaxine, respectively. The assessment was done during the enrolment and at the end of the 3rd, 6th, 9th, and 12th weeks of treatment using the ABC-Hamilton Depression Rating Scale (HAM-D) and Montreal Cognitive Assessment (MoCA) Scale. Statistical Analysis Used: The intragroup analysis was performed using repeated measures ANOVA while intergroup analysis was performed using unpaired “t”-test. p<0.05 was considered statistically significant. Results: Mean HAM-D score was clinically as well as statistically significant at the end of the 12th week of treatment as compared to baseline in both the groups while on the intergroup comparison, there was no statistically significant difference in both groups. The mean MoCA score was (25±2.19) in Group F and (23.76±6.97) in Group V at the end of the 12th week. On intergroup analysis at the 12th week, a statistically significant improvement in cognitive functions was observed in patients Group F as compared to Group V (p<0.05). Conclusions: The study of fluoxetine comparatively better improves cognition functions as compared to venlafaxine.